Clinical presentation and incidence of complications in patients with coeliac disease diagnosed by relative screening. Issue 978 (2nd April 2007) - Sundar, Neela; Crimmins, Rosemary; Swift, Gillian
Abstract : Background: There is an increased prevalence of coeliac disease (CD) among relatives of those with the disease. Aims: To compare the clinical features in patients with CD detected via family screening with those in patients diagnosed routinely. Methods: Information on screening was provided to relatives of patients. Those who wished to be screened were tested for endomysial and/or tissue transglutaminase antibodies. Duodenal biopsy was performed in those with positive antibodies. The clinical details of the relative screening group were compared with those of 105 patients diagnosed routinely. Results: 183 relatives underwent screening, of whom 32 had positive serology, 24 had histology diagnostic of CD, six had normal biopsies and two declined duodenal biopsy. Patients in the relative screening group were younger with a median age of 33 years (range 17–72 years) compared to the routine group which had a median age of 54 years (range 25–88 years). In the relative screening group, there was a male preponderance (M:F ratio 16:8), anaemia at presentation was significantly less common (13% v 58%; p<0.001) and osteoporosis was less frequent (9% v 22%; p<0.244) compared with the routine group. 65% of the relative screening group had gastrointestinal symptoms or anaemia at diagnosis. Conclusions: Patients detected by family screening are younger with a male preponderance, but fewer had anaemia and osteoporosis.